2017
DOI: 10.1371/journal.pcbi.1005776
|View full text |Cite
|
Sign up to set email alerts
|

Features of spatial and functional segregation and integration of the primate connectome revealed by trade-off between wiring cost and efficiency

Abstract: The primate connectome, possessing a characteristic global topology and specific regional connectivity profiles, is well organized to support both segregated and integrated brain function. However, the organization mechanisms shaping the characteristic connectivity and its relationship to functional requirements remain unclear. The primate brain connectome is shaped by metabolic economy as well as functional values. Here, we explored the influence of two competing factors and additional advanced functional req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 75 publications
5
58
0
Order By: Relevance
“…One particularly influential study considered 13 generative models that all incorporated a wiring probability that increased with distance [111]. Consistent with other work, the authors found that the model that only included the wiring minimization constraint was unable to recreate long distance connections of individual connectomes in humans [8,11,111]. Successive generative models were then added that attempted to recreate certain aspects of topology in addition to these geometric constraints [111].…”
Section: Statistics Null Models and Generative Modelsmentioning
confidence: 81%
See 2 more Smart Citations
“…One particularly influential study considered 13 generative models that all incorporated a wiring probability that increased with distance [111]. Consistent with other work, the authors found that the model that only included the wiring minimization constraint was unable to recreate long distance connections of individual connectomes in humans [8,11,111]. Successive generative models were then added that attempted to recreate certain aspects of topology in addition to these geometric constraints [111].…”
Section: Statistics Null Models and Generative Modelsmentioning
confidence: 81%
“…The processes and influences that guide the formation of structural connections in neural systems are disparate and varied [7,8]. Evidence from genetics suggests that neurons with similar functions as operationalized by similar gene expression tend to have more similar connection profiles than neurons with less similar functions [7,9,10].…”
Section: Physical Constraints On Network Topology and Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently and using a different macaque network dataset, ref. 41 suggested that long-distance connections, those unanticipated by a model that penalized the formation of costly connections, form a dense cluster and may also perform some segregative functions.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that our model fits (Figs 4B-E) are in the same range as those reported by Betzel et al (33), indicating that our discrepant results are not due to differences in model accuracy. Finally, while our analysis mimics prior comprehensive evaluations of generative network models based on cost-value trade-offs (32,33), other formulations and approaches are also possible (116)(117)(118) and we cannot completely rule out a role for stochastic processes in shaping hub connectivity. In particular, more abstract models suggest that stochastic wiring, acting in concert with developmental changes in brain geometry and heterogeneous timing of connection formation across regions, can indeed generate networks with brain-like properties (34,71,119).…”
Section: Models Of Brain Network Wiringmentioning
confidence: 99%